Students’ Acceptance and Adoption of Mobile Learning Systems in Higher Education - Kadayat, Suraj; Kharel, Purushottam (Journal of Science and Technology, 2026)
The Mobile learning is creating sharping knowledge and give suitable result. It can useful for creating capabilities of students or learner people. Student can learn the thing anywhere and anytime. Using mobile learning cost can be decrease and the capabilities can be increase. When wireless technology can development and mobile applications also increase so it can help of many people to study like educators, students, teachers and many more people. Now these mobile devices are eye catching and it is one of the novice arena of research. The research aims to examine the factors that can influence the intention of using mobile learning among higher education's students in Nepal. M-leaning has not been widespread in developing countries like Nepal, enriching conventional learning by the extensive use of mobile device is possible in Nepalese institutes of higher educations. If teachers and institutes provide the guidance to use mobile technology, it can change the pedagogy, which supports the teacher. Therefore, M-learning has the potential of being the next prevalent channel of educations in both formal and informal system. To achieve the objective to a survey was conducted among maximum range of 200 students in Kathmandu valley students or out of valley. The research focuses the perceptions to apply unified theory of acceptance and use of technology model (UTAUT). The UTAUT model derived the theoretically integrated model could be applied to study the intentions for implementations of M-learning.